Effect of teriparatide use on bone mineral density and spinal fusion: a narrative review of animal models. (3rd August 2019) - Yolcu, Yagiz; Alvi, Mohammed; Wanderman, Nathan; Carlson, Bayard; Sebastian, Arjun; Bydon, Mohamad; Freedman, Brett
Abstract: Purpose of the study: Teriparatide (Human recombinant Parathyroid Hormone 1-34) is an anabolic agent that is frequently used in patients with osteoporosis and has been extensively investigated with animal model and clinical studies in current literature. The purpose of the study was to evaluate the impact of teriparatide on bone mineral density and fusion. Materials and methods: The findings from preclinical studies that have investigated the role of teriparatide in animal models are summarized in presented review. Results: Overall, the studies show an improvement in bone mineral density and increased fusion rates for osteoporotic animals undergoing spine fusion with teriparatide use. Conclusion: Further studies should be conducted for unanswered questions, such as teriparatide use before surgery, the effect on cervical fusion and surgery related complications.